Simulación de un WCS (Wireless Control System) para sensores y actuadores inteligentes aplicado a procesos productivos. - Bonilla Cuadrado, Alex Javier (2017)
In this project the concepts of Networked Control Systems and Wireless Control Systems (NCS and WCS) are discussed, through which the existence of a network of productive process control interacts In a network environment with multimedia features. It is proposed to simulate the integration of network applications into a shared medium, in which a segment of the network dedicated to control processes uses Wireless technology. Networked control systems and wireless control systems (NCS and WCS) are a technology in development, so the study of their operation and possible applications contribute to determine their limitations, so that to be overcome give way to To devise new forms of communication and new technological devices. The Simulated Network proposes the analysis of the behavior of a network of an industrial environment that coexists with typical applications of an interactive and multimedia network, determining if such a network is viable.